Model Pengembangan Kewirausahaan di Universitas Widya Kartika Surabaya - Muis Murtadho; Robby Kurniawan Budhi; Risma Andini (UNUSA Press, 2018)
Abstract: The large number of unemployed college graduates had become a big problem for the education world. Moreover, the imbalance that happened between the number of job vacancies and the work demands, made many university graduates work in the field which was not in accordance to the knowledge they had learned. In order to overcome these conditions, an entrepreneurial learning needed to be improved in the college. This improvement is hoped to create independent entrepreneurial students based on the acience and technology which later would be able to provide the job opportunities and develop the value of products and services. To achieve this situation, a model of entrepreneurial development which consisted of these three activities: the entrepreneurial education, the internship experience in the association companies, and the entrepreneurial prac- tices was proven in increasing the students’ success of students in starting a business based on science and technology.